Rare encrusted lingulate brachiopods from the Cambrian–Ordovician boundary beds of Baltica. Issue 1 (2nd January 2016) - Vinn, Olev
Abstract : Vinn, O., December 2015. Rare encrusted lingulate brachiopods from the Cambrian–Ordovician boundary beds of Baltica. Alcheringa 40, xx–xx. ISSN 0311-5518 Encrustation is rare on late Cambrian and Tremadocian brachiopods of Baltica. The encrusting fauna is represented by a single taxon, Marcusodictyon . Only Schmidtites celatus is encrusted in the Furongian of Estonia. The Marcusodictyon – Schmidtites association is the earliest example of syn vivo encrustation and symbiosis from the Baltica palaeocontinent. The encrusting faunas of the late Cambrian and Tremadocian of Baltica were unusual presumably owing to palaeogeographic reasons because the other known examples of early encrustation originate from lower palaeolatitudes. Olev Vinn [ olev.vinn@ut.ee ], Department of Geology, University of Tartu, Ravila 14A, 50411 Tartu, Estonia .